Developing a Contextually Relevant Concept of Regional Hegemony: The Case of South Africa, Zimbabwe and "Quiet Diplomacy" - Miriam Prys (German Institute of Global and Area Studies (GIGA), 2008)
South Africa's 'quiet diplomacy' has been often used to reject the notion of South African leadership or regional hegemony in southern Africa. This article finds that this evaluation is founded on a misguided understanding of regional hegemony, which is based on conventional hegemony theories that are mostly derived from the global role of the United States after World War II. Alternatively, this article uses a concept of hegemony that, for example, takes into account the 'regionality' of South Africa's hegemony, which both allows external actors to impact on regional relations and allows South Africa to pursue its foreign policy goals on the global level of international politics. This concept helps to systemically analyze South Africa's foreign policy in the Zimbabwean crisis and to better integrate this policy into the broader framework of its regional and global ambitions. – – Die Idee südafrikanischer Hegemonie wird häufig mit dem Hinweis darauf abgelehnt, dass Präsident Mbekis 'stille Diplomatie' gegenüber Simbabwe gescheitert sei. In diesem Beitrag wird im Gegensatz dazu argumentiert, dass eine solche Ablehnung hauptsächlich auf einem Missverständnis des Konzeptes von Regionalhegemonie beruht. Das Konzept wird gewöhnlich im Sinne konventioneller Auffassungen von Hegemonie verwendet, die fast ausschließlich von globaler, US-amerikanischer Hegemonie abgeleitet wurden. Dies vernachlässigt, dass Südafrikas Hegemonie auf regionaler Ebene stattfindet, was beispielsweise externen Akteuren per Definition erlaubt, Einfluss auf die Region zu nehmen. Südafrika kann ebenfalls nicht nur auf der regionalen Ebene agieren, sondern außenpolitische Ziele auch auf der globalen Ebene verfolgen. Werden diese und andere Faktoren einbezogen, kann dies hilfreich sein, um die südafrikanische Politik gegenüber Simbabwe im Gesamtzusammenhang von Südafrikas regionalen und globalen Ambitionen systematisch zu analysieren.
Keywords: 300; regional powers; hegemony; South Africa; Zimbabwe; quiet diplomacy